Technological innovation in the Italian school. A critical and historical analysis - Moricca, Camilla (Form@re - Open Journal per la formazione in rete, 2016)
Technological introduction into school takes place in the form of innovations that maintaining low awareness and memories of the previous phases. The work recalls briefly the main institutional initiatives and best-known theories of reference in order to foster a historical-critical awareness of what the experience may have informed us. In the last part we focus on references in vogue, such as coding and robotics, wondering if they are really innovations and if they are based on valid educational criteria. L’innovazione tecnologica nella scuola italiana. Per un’analisi critica e storica L’introduzione tecnologica nella scuola è caratterizzata da ondate che si succedono conservando scarsa consapevolezza e ricordo della fase precedente. Il lavoro ripercorre in modo sintetico le principali iniziative istituzionali e le più note teorie di riferimento che le hanno accompagnate nell’ottica di favorire una consapevolezza storico-critica su ciò che l’esperienza ci può aver insegnato. Nell’ultima parte ci si sofferma su riferimenti oggi in voga, quali il coding e la robotica, chiedendoci se siano davvero nuovi e se poggino su criteri pedagogici fondati.